Gold Nanoparticles: Optical Properties and Cancer Diagnosis Uses and Phototherapy: Exploring the Optical Properties and Applications of Gold Nanoparticles in Cancer Diagnosis and Phototherapy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The application of plasmonic gold nanoparticles for cancer diagnosis and photothermal therapy is currently a common field of nanomedicine, due to the interesting optical properties of the nanoparticles. The resonance of the surface plasmon, a peculiar phenomenon of plasmonic (noble metal) nanoparticles, results in intense electromagnetic fields at the edge of particles and thus improves all radiative properties such as absorption and dispersion.Therefore, a variety of systems which are not radiative transform the strongly absorbed light rapidly to heat. In this study, we examine these are basic infrared and photothermic characteristics in various types and structures of gold nanoparticles and discuss its latest cancer programs imaging, spectroscopic detection and phototherapy.